2003
DOI: 10.1021/ma021785r
|View full text |Cite
|
Sign up to set email alerts
|

Fast Monomers:  Factors Affecting the Inherent Reactivity of Acrylate Monomers in Photoinitiated Acrylate Polymerization

Abstract: A systematic study on the effect of molecular structure on the photoinitiated polymerization of acrylates was undertaken. Initially, the research was focused on the effect of hydrogen bonding, and it was found that preorganization via hydrogen bonding enhances the maximum rate of polymerization (R p). This hydrogen bonding facilitated preorganization also affected the tacticity of the resultant polymer. Next, the effect of polarity as represented by the calculated dipole moment (μcalc) of a given monomer was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 75 publications
11
162
1
Order By: Relevance
“…The variation in reaction time required to achieve 100 Å polymer thickness might be due to differences in inherent reactivity and solvation of the monomers (Ouchi et al 2011), which is strongly influenced by their molecular structure. PHEMA-co-PEG10MA showed the fastest reaction time, as a result of the high solubility of HEMA and PEG10MA monomers in the water-methanol solvent due to the high availability of hydrogen bond acceptor atoms, which facilitates pre-organization of monomers resulting in higher monomer propagation (Jansen et al 2003). In addition, the larger monomer size of PEG10MA might also contribute to achieving 100 Å of PHEMA-co-PEG10MA layer thickness faster than for the smaller monomers.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in reaction time required to achieve 100 Å polymer thickness might be due to differences in inherent reactivity and solvation of the monomers (Ouchi et al 2011), which is strongly influenced by their molecular structure. PHEMA-co-PEG10MA showed the fastest reaction time, as a result of the high solubility of HEMA and PEG10MA monomers in the water-methanol solvent due to the high availability of hydrogen bond acceptor atoms, which facilitates pre-organization of monomers resulting in higher monomer propagation (Jansen et al 2003). In addition, the larger monomer size of PEG10MA might also contribute to achieving 100 Å of PHEMA-co-PEG10MA layer thickness faster than for the smaller monomers.…”
Section: Resultsmentioning
confidence: 99%
“…[7] This carbonate coupler can be functionalized with polymers or other functional molecules containing primary amine groups. A selective functionalization of the carbonate coupler could be assured because the reactivity of the carbonate groups is significantly different.…”
Section: Pdms With Ammonium End Groupsmentioning
confidence: 99%
“…Other theories proposed include hydrogen bonding, through which increased reactivity resulted from the enhanced propagation efficiency via pre-organized double bonds [29], and resonance effects that lead to the increased reactivity of propagating radicals [21]. It was reported that the observed enhanced reactivity of the novel monomers is caused by the combination of the proposed explanations [30].…”
Section: Discussionmentioning
confidence: 99%